2005
DOI: 10.1590/s0034-89102005000100004
|View full text |Cite
|
Sign up to set email alerts
|

Fontes alimentares de Triatoma pseudomaculata no Estado do Ceará, Brasil

Abstract: Resumo ObjetivoTriatoma pseudomaculata, espécie peridomiciliar, é encontrada apresentando baixa taxa de infecção por Trypanosoma cruzi. Com o objetivo de identificar os possíveis reservatórios de T. cruzi, investigou-se a ocorrência desse triatomíneo no domicílio, bem como suas fontes alimentares. Métodos De janeiro de 2001 a julho de 2002 foram capturados 921 espécimes de T. pseudomaculata em 13 municípios do sul do Estado do Ceará. O conteúdo intestinal dos triatomíneos foi retirado, espalhado em disco de pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
(4 reference statements)
0
10
0
2
Order By: Relevance
“…Despite being refractory to Trypanosoma cruzi, these domestic fowl have already been reported as responsible for maintaining triatomine colonies in peridomestic environments, serving as a food source and affording the emergence of abundant populations of these vectors in proximity to humans. 4,13,14 In this study, the finding of human DNA in a Triatoma brasiliensis fifth nymph instar specimen captured inside a house is worrisome, indicating resident bugs feeding on humans. Valença-Barbosa and others 15 highlighted that bug numbers based on capture are rather underestimated.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Despite being refractory to Trypanosoma cruzi, these domestic fowl have already been reported as responsible for maintaining triatomine colonies in peridomestic environments, serving as a food source and affording the emergence of abundant populations of these vectors in proximity to humans. 4,13,14 In this study, the finding of human DNA in a Triatoma brasiliensis fifth nymph instar specimen captured inside a house is worrisome, indicating resident bugs feeding on humans. Valença-Barbosa and others 15 highlighted that bug numbers based on capture are rather underestimated.…”
mentioning
confidence: 65%
“…The high prevalence of goats as a food source in several kinds of ecotopes might be explained by the high mobility of these animals to graze, which was already mentioned, 5,11 with evidences of triatomine blood meals based on field observation and serological tests (precipitin 4 and ELISA…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Triatoma pseudomaculata has been found associated with cockroaches inside chicken-coops (Freitas et al 2005), and precipitin tests confirmed the presence of cockroach hemolymph in the intestinal contents of some of the sampled insects. Our work tested whether T. pseudomaculata presents behavioral traits indicative of arthropod feeding.…”
Section: Triatoma Pseudomaculata Corrêa and Espínola Is A Hematophagousmentioning
confidence: 84%
“…This species was often found in domiciles in Planaltina and Paranoá, and in some of these domiciles nymphs were collected, indicating colonization. Even though T. pseudomaculata is more frequent in peridomicile and usually feeds on birds, the colonization in domiciles has been observed in Sobral, Ceará, and Berilo, Minas Gerais, suggesting adaptation of this species in this environment 25,43 . In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 .…”
Section: Discussionmentioning
confidence: 99%